DWI and complex brain network analysis predicts vascular cognitive impairment in spontaneous hypertensive rats undergoing executive function tests - López-Gil, Xavier; Amat-Roldan, Iván; Tudela, Raúl; Castañé, Anna; Prats-Galino, Alberto; Planas, Anna M.; Farr, Tracy D.; Soria, Guadalupe (Frontiers in Aging Neuroscience, 2014)
The identification of biomarkers of vascular cognitive impairment is urgent for its early diagnosis. The aim of this study was to detect and monitor changes in brain structure and connectivity, and to correlate them with the decline in executive function. We examined the feasibility of early diagnostic magnetic resonance imaging to predict cognitive impairment before onset in an animal model of chronic hypertension: Spontaneously Hypertensive Rats. Cognitive performance was tested in an operant conditioning paradigm that evaluated learning, memory and behavioral flexibility skills. Behavioral tests were coupled with longitudinal diffusion weighted imaging acquired with 126 diffusion gradient directions and 0.3 mm3 isometric resolution at 10, 14, 18, 22, 26 and 40 weeks after birth. Diffusion weighted imaging was analyzed in 2 different ways, by regional characterization of diffusion tensor imaging indices, and by assessing changes in structural brain network organization based on Q-Ball tractography. Already at the first evaluated times, diffusion tensor imaging scalar maps revealed significant differences in many regions, suggesting loss of integrity in white and grey matter of spontaneously hypertensive rats when compared to normotensive control rats. In addition, graph theory analysis of the structural brain network demonstrated a significant decrease of hierarchical modularity, global and local efficacy, with predictive value as shown by regional 3-fold cross validation study. Moreover, these decreases were significantly correlated with the behavioral performance deficits observed at subsequent time points, suggesting that the diffusion weighted imaging and connectivity studies can unravel neuroimaging alterations even overt signs of cognitive impairment become apparent.